1978
DOI: 10.1037/0097-7403.4.2.104
|View full text |Cite
|
Sign up to set email alerts
|

Habituation of the forelimb-withdrawal response in neonatal rats.

Abstract: The purpose of the present research was to examine the ontogeny of habituation in the neonatal rat, using the forelimb-withdrawal response. Thresholds and latencies of the response, changing patterns of responding to shock stimuli, and habituation of the response were studied in rats 3 to 15 days of age. It was found that although response thresholds do not change during this period of development, response latencies decrease and amplitudes increase. Three- and 6-day old pups remain active much longer followin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
42
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 22 publications
1
42
0
Order By: Relevance
“…Additional species exhibiting a similar phenomenon include nonhuman primates (Harlow and Harlow, 1965), dogs [Fisher (1955), cited in Rajecki et al (1978)], and humans (Helfer et al, 1997). Our imprinting model in rat pups uses a fearconditioning paradigm in which odor paired with 0.5 mA shock paradoxically causes an odor preference during a temporally defined sensitive period (Sullivan et al, 1986a(Sullivan et al, ,b, 2000aCamp and Rudy, 1988;Moriceau and Sullivan, 2004b;Roth and Sullivan, 2005), although pups clearly show pain-related responses during shock (Stehouwer and Campbell, 1978;Emerich et al, 1985;Barr, 1995;Sullivan et al, 2000a). Our data suggest the amygdala does not participate in the sensitive-period odor-shock conditioning that may underlie the pups' attenuated aversion learning (Sullivan et al, 2000a;Moriceau and Sullivan, 2004b;Roth and Sullivan 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Additional species exhibiting a similar phenomenon include nonhuman primates (Harlow and Harlow, 1965), dogs [Fisher (1955), cited in Rajecki et al (1978)], and humans (Helfer et al, 1997). Our imprinting model in rat pups uses a fearconditioning paradigm in which odor paired with 0.5 mA shock paradoxically causes an odor preference during a temporally defined sensitive period (Sullivan et al, 1986a(Sullivan et al, ,b, 2000aCamp and Rudy, 1988;Moriceau and Sullivan, 2004b;Roth and Sullivan, 2005), although pups clearly show pain-related responses during shock (Stehouwer and Campbell, 1978;Emerich et al, 1985;Barr, 1995;Sullivan et al, 2000a). Our data suggest the amygdala does not participate in the sensitive-period odor-shock conditioning that may underlie the pups' attenuated aversion learning (Sullivan et al, 2000a;Moriceau and Sullivan, 2004b;Roth and Sullivan 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Before this age, odor-shock associations paradoxically induce an odor preference (Stehouwer and Campbell 1978;Haroutunian and Campbell 1979;Camp and Rudy 1988;Sullivan et al 2000) despite pups feeling pain from shock (Collier and Bolles 1980;Barr 1995;Fitzgerald 2005). The neural network sustaining this paradoxical preference involves OB and anterior piriform cortex (aPCx) whereas the amygdala does not appear to participate in the circuit (Sullivan and Wilson 1995;Roth and Sullivan 2005;Moriceau et al 2006).…”
mentioning
confidence: 99%
“…Haroutunian and Campbell (1979) demonstrated that moderately painful shock could not support aversion learning in neonatal rat pups unless it was delivered intraperitoneally, although higher shock (>1.0 mA) readily produced an odor aversion in very young pups (Kucharski and Spear 1984;Miller et al 1990a;Sullivan and Wilson 1995). While lower shock levels are painful to pups (Stehouwer and Campbell 1978;Collier and Bolles 1980;Emerich et al 1985;Sullivan et al 2000a), they paradoxically produce an odor preference in pups younger than PN10-12 (Sullivan et al 1986;Camp and Rudy 1988), apparently due to the amygdala's failure to participate during the conditioning (Sullivan et al 2000a).These data suggest that pups have access to at least two neural pathways for odor-aversion learning, although each has a different developmental time course. To test this, we made a direct neurobehavioral comparison of LiCl-induced odor aversion, 1.2-mA shock-induced odor aversion, and the 0.5-mA shock that produces a preference in young pups but an aversion in older pups.…”
mentioning
confidence: 99%